The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1981
DOI: 10.1159/000182017
|View full text |Cite
|
Sign up to set email alerts
|

Tissue and Blood Cell Concentration of Methylguanidine in Rats and Patients with Chronic Renal Failure

Abstract: Methylguanidine concentration in blood cell of nondialysed patients with chronic renal failure was quantitatively determined by the method of the present authors. We also determined tissue methylguanidine concentrations in the liver, blood cell, kidney, colon, muscle and brain of uremic rat experimentally produced by Platt’s method. Methylguanidine concentrations in blood cell and tissues except the brain of the uremic rats and in blood cell of the uremic patients were 5–7 times higher than those in their seru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
1

Year Published

1983
1983
2002
2002

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 6 publications
(18 reference statements)
1
16
1
Order By: Relevance
“…Recently, NO synthase inhibitors have been isolated from plasma of healthy volunteers [22]. It was demonstrated in rats and in humans [23, 24, 25] that these endogenous inhibitors accumulate gradually along with the progression of renal failure in plasma and within different tissues (kidney, liver, muscle, and brain). All this may explain the correlation between the NO production and the degree of renal failure in our patients.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, NO synthase inhibitors have been isolated from plasma of healthy volunteers [22]. It was demonstrated in rats and in humans [23, 24, 25] that these endogenous inhibitors accumulate gradually along with the progression of renal failure in plasma and within different tissues (kidney, liver, muscle, and brain). All this may explain the correlation between the NO production and the degree of renal failure in our patients.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to the synthesizing organ, gut flora [4], liver [9,10] and muscle [10] are considered possibilities. However, these studies were long-term experiments in which creatinine or other possible precursors were ad ministered chronically or animals with chronic renal fai lure were used.…”
Section: Discussionmentioning
confidence: 99%
“…In this study creatinine was administered to normal rats as a precursor of MG synthesis because it is known to stimulate MG synthesis. It has been reported that the concentrations of MG in blood cells and other tissues except the brain of uremic rats are higher than that in plasma [2,9]. Because of the possibility that, in a long-term experiment, MG synthesized in some other organ might enter another organ via plasma, various tissues, i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas nearly 100 different guanidino compounds have been found in the natural world, those found in the serum and urine of patients with renal failure include guanidine, guanidinosuccinic acid, guanidinopropionic acid, guanidinoacetic acid, arginine, creatinine (Cr), creatine, and methylguanidine (MG). Among these compounds, MG has been studied from various aspects in relation to its toxicity [9, 10], quantification [11], precursor [12, 13, 14], organs where it is produced [15, 16, 17], production pathways [18, 19, 20, 21, 22], factors influencing its production [23, 24, 25], etc. However, few studies have examined the specific location of MG production in the kidney and the factors involved in its production.…”
Section: Introductionmentioning
confidence: 99%